2010
DOI: 10.1038/hdy.2010.51
|View full text |Cite
|
Sign up to set email alerts
|

Inherited XX sex reversal originating from wild medaka populations

Abstract: The teleost fish, medaka (Oryzias latipes), has an XX/XY sexdetermining mechanism. A Y-linked DM domain gene, DMY, has been isolated by positional cloning as the sex-determining gene in this species. Previously, we conducted a field survey of genotypic sex and found that approximately 1% of wild medaka are sex-reversed (XX males and XY females). Here, we performed genetic analyses of nine spontaneous XX sexreversed males to elucidate its genetic basis. In all cases, the F 1 progeny were all females, whereas XX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Particularly, epistatic effects may be relevant because a single gene acting upstream or even downstream of a preexisting SD gene (SDg) may take the control of gonad fate, thus, masking extant genetic variation at other involved loci. Epistatic interactions have been reported between major SD loci in different fish groups (Cnaani et al, 2008; Ser et al, 2010; Parnell and Streelman, 2013), and also epistatic allelic variants have been reported segregating in populations of species with a well known SD genetic system like medaka ( Oryzias latipes ; Shinomiya et al, 2010). In fact, notable interactions occur between gene products at the initial stages of gonad development such as the suppression of wnt4 and β -catenin, key genes for ovarian development, by sox9 and fgf9 (Nef and Vassalli, 2009); the modulation of gonadal aromatase (cypb19a), responsible of the balance between androgens and estrogens, by the action of other genes or environmental factors such as temperature (Navarro-Martín et al, 2011); or the interaction between the anti-müllerian hormone (amh1) and its receptor (amhr2), which triggers an essential signaling pathway for testis development (Kamiya et al, 2012).…”
Section: Genetic Architecture Of Sex Determination In Fishmentioning
confidence: 99%
“…Particularly, epistatic effects may be relevant because a single gene acting upstream or even downstream of a preexisting SD gene (SDg) may take the control of gonad fate, thus, masking extant genetic variation at other involved loci. Epistatic interactions have been reported between major SD loci in different fish groups (Cnaani et al, 2008; Ser et al, 2010; Parnell and Streelman, 2013), and also epistatic allelic variants have been reported segregating in populations of species with a well known SD genetic system like medaka ( Oryzias latipes ; Shinomiya et al, 2010). In fact, notable interactions occur between gene products at the initial stages of gonad development such as the suppression of wnt4 and β -catenin, key genes for ovarian development, by sox9 and fgf9 (Nef and Vassalli, 2009); the modulation of gonadal aromatase (cypb19a), responsible of the balance between androgens and estrogens, by the action of other genes or environmental factors such as temperature (Navarro-Martín et al, 2011); or the interaction between the anti-müllerian hormone (amh1) and its receptor (amhr2), which triggers an essential signaling pathway for testis development (Kamiya et al, 2012).…”
Section: Genetic Architecture Of Sex Determination In Fishmentioning
confidence: 99%
“…XX medaka develop into females while XY medaka with DMY/dmrt1bY on the Y chromosome become males. In the wild, however, sex reversal (both male-to-female and femaleto-male) is frequently observed among medaka (Shinomiya et al, 2004(Shinomiya et al, , 2010. It was recently reported that environmental factors may affect the phenotypic sex of medaka.…”
Section: Introductionmentioning
confidence: 99%
“…LG8 [Shinomiya et al, 2010]. The absence of the Y chromosome in successive generations of medaka from the Shirone wild population suggests that LG8 has taken over the role of the sex chromosomes [Shinomiya et al, 2010].…”
Section: Sex Reversal In the Wildmentioning
confidence: 99%
“…The absence of the Y chromosome in successive generations of medaka from the Shirone wild population suggests that LG8 has taken over the role of the sex chromosomes [Shinomiya et al, 2010]. The genetic basis of XY lacking dmy resulting in male-tofemale sex reversal was found to be of 2 types, one due to mutations in the amino acid coding sequence of dmy and the other due to low expressions of dmy at 0 days after hatching at the critical sex-determining period while the coding sequence was normal [Otake et al, 2006].…”
Section: Sex Reversal In the Wildmentioning
confidence: 99%